Dimethyl α-ketoglutarate ameliorates cisplatin-induced acute kidney injury by modulating mitophagy through the PINK1/Parkin pathway - Haijing Dou; Huihui Hao; Ruoyi Zhao; Hailun Li; Fangshu Wei; Yong Xu; Donghui Zheng; Juan Xie; Xiang Li (European Journal of Medical Research)
Abstract Background Mitochondrial dysfunction and abnormal energy metabolism are key determinants of the progression of acute kidney injury (AKI). α-Ketoglutarate (AKG) is an intermediate metabolite of the tricarboxylic acid cycle and plays a crucial role in energy metabolism and amino acid synthesis. However, the role of AKG in AKI therapy remains incompletely understood. Methods Cisplatin (CIS) was employed to establish acute kidney injury models in mice and cells, with DM-AKG administered as an intervention. Network pharmacology was utilized to predict the target genes and pathway enrichment of AKG in the treatment of AKI. Apoptosis was assessed using flow cytometry, and cell viability was determined via the CCK-8 assay. The levels of intracellular reactive oxygen species (ROS) and mitochondrial membrane potential (MMP) were assessed using optical microscopy. Renal function was evaluated using absorbance spectroscopy. Hematoxylin–eosin (H&E) staining was used to examine the pathological changes in renal tissues across different groups. The ultrastructure of mitochondria was examined using transmission electron microscopy. Protein expression levels of KIM-1, Caspase-3, DRP1, MFN1, PINK1, and Parkin were evaluated using Western blot analysis. The expression of PINK1 and Parkin was examined by immunohistochemistry. Results Herein, we demonstrate that dimethyl α-ketoglutarate (DM-AKG), an AKG derivative with favorable cell membrane permeability, effectively ameliorates cisplatin (CIS)-induced AKI. Further network pharmacological analyses revealed that AKG could treat AKI through 91 potential targets of action. Moreover, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses showed significant enrichment of pathways related to mitochondria and energy metabolism. Furthermore, in a CIS-treated HK-2 cell model, we found that exogenous DM-AKG supplementation improved mitochondrial dynamics (increased expression of the mitochondrial fusion protein MFN1 and decreased expression of the mitochondrial fission protein DRP1), increased mitochondrial membrane potential, and decreased reactive oxygen species generation. Consistent with these findings, in the CIS-AKI mouse model, DM-AKG similarly improved mitochondrial morphology, structure, and dynamics, as well as increased mitophagy observed by electron microscopy. Conclusion These results suggest that DM-AKG may exert a therapeutic effect on AKI by improving mitochondrial function. Regarding the molecular mechanism, we confirmed that DM-AKG could increase mitophagy and promote the clearance of damaged mitochondria by activating the PINK1/Parkin pathway, which could play a protective role in the kidney. In conclusion, our study provides a novel strategy for the effective treatment of AKI.